2019
DOI: 10.1371/journal.pone.0212936
|View full text |Cite|
|
Sign up to set email alerts
|

Occurrence and characterization of quinolone resistant Escherichia coli from Norwegian turkey meat and complete sequence of an IncX1 plasmid encoding qnrS1

Abstract: Plasmid-mediated quinolone resistance (PMQR) is frequent among Escherichia coli from various food products and animals in several countries. The objective of this study was to characterize quinolone resistant E. coli (QREC) from Norwegian turkey meat regarding resistance profiles, genetic mechanisms for quinolone resistance, genetic relatedness, and to investigate whether PMQR genes were present. In total, 78 QREC were isolated by a selective method from 156 samples throughout 2013. Isolates were subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
2
19
1
Order By: Relevance
“…Results of this study demonstrated that only minority (8.8%) of the isolates possessed PMQR genes and analysis of genes revealed that qnrS1 most frequently identified mechanism, followed by aac(6′)‐1b‐cr . The low presence of PMQR in this study is consistent with the findings from foods of animal origin in Norway (0–1.3%; Kaspersen et al, 2020; Slettemeås et al, 2019) and in Tunisia (17.6%; Kilania et al, 2020). Additionally, this is also consistent with the findings in human clinical practice in France (24/507; 4.7%; Muggeo et al, 2020), in Korea (10.7%; Kim et al, 2020), and in Taiwan (14.9%; Kao et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Results of this study demonstrated that only minority (8.8%) of the isolates possessed PMQR genes and analysis of genes revealed that qnrS1 most frequently identified mechanism, followed by aac(6′)‐1b‐cr . The low presence of PMQR in this study is consistent with the findings from foods of animal origin in Norway (0–1.3%; Kaspersen et al, 2020; Slettemeås et al, 2019) and in Tunisia (17.6%; Kilania et al, 2020). Additionally, this is also consistent with the findings in human clinical practice in France (24/507; 4.7%; Muggeo et al, 2020), in Korea (10.7%; Kim et al, 2020), and in Taiwan (14.9%; Kao et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…For example, a recent study by Obaidat, Bani Salman, Davis, and Roess (2018) has reported a 3.8% resistance rate for ciprofloxacin among intestinal E. coli isolates from fecal samples of healthy dairy cattles in Jordan (Obaidat et al, 2018). The results for occurrence rates cannot be directly comparable with previous studies, as the current study increased the sensitivity of test by using overnight enrichment and selective media with ciprofloxacin disk, which has been previously demonstrated to affect the outcome (Slettemeås et al, 2019). A recent Italian study involving 67 herds has found E. coli in 32.8% of BTM samples (Dell'Orco et al, 2019).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Resistance to these antimicrobials has previously been associated with qnrS1 (53). qnrS1 have previously been identified on large conjugative plasmids harbouring bla TEM-1B and tetA (54,55), which supports the significant positive correlations between qnrS1, bla TEM-1B and tetA. On the other hand, qnrB19 have been encoded on small, non-conjugative plasmids without any other resistance genes (56).…”
Section: Downloaded Frommentioning
confidence: 63%
“…Resistance can also develop from mutations of regulatory elements resulting in reduced influx or increased efflux of quinolones (Tavío del et al, 1999;Kern et al, 2000) or through acquisition of plasmid mediated quinolone resistance (PMQR) determinants, including qnr, oqxAB, qepA or aac(6 )-Ib-cr (Gosling et al, 2012;Machuca et al, 2014Machuca et al, , 2016Yamasaki et al, 2015). Additionally, PMQR determinants have been shown to coexist with resistance genes causing resistance toward other antimicrobials, which enables co-selection (Huang et al, 2012;Slettemeås et al, 2019). Quinolone resistance frequently develop in a stepwise fashion, where a single mutation in gyrA is often the initial step (Huseby et al, 2017).…”
Section: Introductionmentioning
confidence: 99%